An Approach of Power Factor Correction in BLDC Motor Drives Using Cuk Derived Converters - R. Balamurugan; J. Pearly Catherine (Institute of Advanced Engineering and Science, 2014)
This paper deals with a comparative analysis of various converter topologies for Power Factor Correction (PFC) in BLDC motor drives. A power factor corrected converter is required for improving power quality at the AC mains of an inverter fed BLDC motor drive. Conventionally, the BLDC motor is fed by a diode bridge rectifier (DBR) which results in highly distorted supply current and a poor power factor. A new bridgeless single-phase ac–dc Cuk derived topology has been introduced for power factor correction. This bridgeless topology uses minimum number of switches and thus reduces the less conduction losses compared with the conventional PFC rectifier. There are three cuk derived configurations for power factor correction. In this paper, all the cuk derived topologies are investigated and compared. The best topology is identified and recommended for PFC in BLDC motor drive.